2022
DOI: 10.1155/2022/8974924
|View full text |Cite|
|
Sign up to set email alerts
|

A Meta-Analysis of the Differences in Serum Lipid Levels between Pregnant Women with Hypertensive Disorder Complicating Pregnancy and Nonhypertensive Disorder Complicating Pregnancy

Abstract: Background. Although a lot of research work has been done on the etiology and pathogenesis of hypertensive disorder complicating pregnancy at home and abroad, the exact etiology and pathogenesis of the disease are still uncertain so far. Aims. Systematic review of meta-analysis of differences in serum lipid levels between pregnant women with hypertensive disease complicated with pregnancy and nonhypertensive disease complicated with pregnancy. Materials and Methods. PubMed, Medline, Embase, Science Citation In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%